2020
DOI: 10.1002/ldr.3440
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of restoration approaches on the Inner Mongolian Steppe based on criteria of the Society for Ecological Restoration

Abstract: Ecological restoration is becoming an increasingly common management tool worldwide. However, a challenge still exists on how to effectively monitor restoration outcomes and evaluate restoration success for ecological restoration managers. In this review, the goal is to evaluate whether the research in a degraded area has been sufficient for fostering efficient restoration measures and follow‐up of restoration success based on the Society for Ecological Restoration (SER) criteria. We selected the Inner Mongoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 82 publications
0
4
1
Order By: Relevance
“…Our long-run analyses suggested that predicted burned grassland extent is insensitive to change in maximum temperature, vapor pressure deficit, precipitation, or relative humidity. These findings contrast with studies that predict increased fire impacts in north-eastern China in response to higher maximum temperature, decreased precipitation, greater vapor pressure deficit, and lower humidity 28 , 44 47 . We posit four potential explanations for this divergence: First, although inter-annual precipitation outside the fire season varies significantly in Xilingol grasslands, little precipitation arrives during the fire season itself.…”
Section: Resultscontrasting
confidence: 99%
“…Our long-run analyses suggested that predicted burned grassland extent is insensitive to change in maximum temperature, vapor pressure deficit, precipitation, or relative humidity. These findings contrast with studies that predict increased fire impacts in north-eastern China in response to higher maximum temperature, decreased precipitation, greater vapor pressure deficit, and lower humidity 28 , 44 47 . We posit four potential explanations for this divergence: First, although inter-annual precipitation outside the fire season varies significantly in Xilingol grasslands, little precipitation arrives during the fire season itself.…”
Section: Resultscontrasting
confidence: 99%
“…For example, connectivity projects in Australia and New Zealand attempt to connect forest fragments and rely on local support to implement the programme with public and private funding. Major afforestation projects in China may have increased forest cover (data in some cases are unreliable), but in the past have used non-native species and may have removed local farmers without providing them with alternatives [ 141 , 260 , 267 , 268 ], although there is increasing emphasis on using native species [ 269 – 271 ]. Other landscape approaches, such as the Great Green Wall in Africa, eventually may be part of BC commitments of some of the countries, but so far these have not been solidified.…”
Section: Discussionmentioning
confidence: 99%
“…The geographical components (i.e., those that are manifestly spatial in their impacts) include both natural elements under global environmental change and socioeconomic elements associated with the characteristics of national and regional development. These components are affected by interactions between sets of processes, for example, physical processes such as warming and evaporation, economic processes such as traveling and consumption, or social-ecological processes such as strip mining and land degradation (Zhang et al, 2020a(Zhang et al, , 2020b(Zhang et al, , 2022dThomaz et al, 2022;Zhao et al, 2020a). These spatially explicit physical, ecological, and social processes tend to be generalized as geographical processes (Fu, 2020), and influenced by landscape restoration projects (Fu et al, 2021a;Liu, 2020;Tikadar et al, 2022;Fan et al, 2021;Liao et al, 2018).…”
Section: The Response Of Geographical Processes To Landscape Restorationmentioning
confidence: 99%